Stress-induced g shifts of r, levels for rare- earth ions. - Calvo, R.; Oseroff, S. B.; Fainstein, M.; Passeggi; Tovar, M. (American Chemical Society's, 1974)
Fil: Calvo, R. Comisión Nacional de Energía Atómica; Argentina